Candida Albicans CT Value in Asthmatics with Prolonged Corticosteroid Inhaler Uses - Cholidah, Ema Zahiroh Nur; Sasongkowati, Retno; Rahayuningsih, Christ Kartika; Suliati, Suliati (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
Corticosteroid inhaler is one of the first-line drugs given for the control and prevention of asthma attacks in the long term and continuously. The use of corticosteroid inhalers for a long time has systemic side effects in the oral cavity which can be a predisposing factor for normal fungal infection of Candida albicans microflora, an increase of Candida albicans’s amount in the oral cavity can cause oral candidiasis. Candida albicans detection using q-PCR to detect specific genes in oral swab specimens can provide an indirect picture of the amount of Candida albicans in the samples taken. The purpose of this study was to determine the relationship between the length of use of corticosteroid inhalers and the cycle threshold value in oral swab samples of asthma patient. This type of research is correlational research with data collection techniques using a purposive sampling technique on 30 respondents at the Lung Polyclinic at Bhayangkara Hospital H.S Samsoeri Mertojoso Surabaya who fit the inclusion criteria. Samples were examined using q-PCR to detect specific genes in the ITS-2 region to detect Candida albicans. This research was conducted at the Molecular Biology Laboratory of theMinistry of Health Surabaya Polytechnic during the period April – May 2023. The results showed that there were 26 samples(86.7%) positive for the ITS-2 gene and 4 samples (13.3%) negative for the ITS-2 gene. with sig. 0.307 so that it can be concluded that there is no relationship between the length of use of corticosteroid inhalers and the cycle threshold value of C. albicans in asthmatic’s oral swab sample.